From AKP's 'Conservative Democracy' to 'Advanced Democracy': Shifts and Challenges in the Debate on 'Europe'. Issue 1 (2nd January 2016) - Alpan, Başak
Abstract: Following the AKP's victory in the 2002 general elections, 'conservative democracy' has emerged as a trademark in Turkish politics, focusing on cosmopolitanism and European integration. In the late 2000s, the party's favourite notion was 'advanced democracy', this time underlining Turkey's leadership claim in the region and displaying a more critical approach to 'Europe'. In this paper, I aim to show how different narratives on 'Europe' emerged within the context of these empty signifiers. The paper claims that the difference in the two narratives on 'Europe' in two different periods does not point to a complete and fully fledged de-Europeanisation trend.